2014
DOI: 10.1002/2013jd020934
|View full text |Cite
|
Sign up to set email alerts
|

Observational tests of hurricane intensity estimations using GPS radio occultations

Abstract: This study presents a novel approach to estimating the intensity of hurricanes using temperature profiles from Global Positioning System radio occultation (GPSRO) measurements. Previous research has shown that the temperature difference between the ocean surface and the eyewall outflow region defines hurricanes' thermodynamic efficiency, which is directly proportional to the storm's intensity. Outflow temperatures in the eyewall region of 27 hurricanes in 2004-2011 were obtained from GPSRO observations. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 57 publications
0
17
0
Order By: Relevance
“…Values of 0.3emtrue0.3emṠr are computed from the satellite data by using the relation, 0.3emtrue0.3emṠr=ρg0HRwTenormaldz, with three additive terms: one for rain, one for graupel, and one for snow. For the vertical profile of the temperature in the eyewall, T e ( z ), we use T e ( z ) = T s −6.5 z , where z is measured in kilometers [ Vergados et al , ]. Values of V are obtained from the National Hurricane Center's extended best track database [ Demuth et al , ].…”
Section: Thermodynamics Of Rainpowermentioning
confidence: 99%
“…Values of 0.3emtrue0.3emṠr are computed from the satellite data by using the relation, 0.3emtrue0.3emṠr=ρg0HRwTenormaldz, with three additive terms: one for rain, one for graupel, and one for snow. For the vertical profile of the temperature in the eyewall, T e ( z ), we use T e ( z ) = T s −6.5 z , where z is measured in kilometers [ Vergados et al , ]. Values of V are obtained from the National Hurricane Center's extended best track database [ Demuth et al , ].…”
Section: Thermodynamics Of Rainpowermentioning
confidence: 99%
“…Wong and Emanuel (2007), Luo et al (2008) and Vergados et al (2013) demonstrated that there is a connection between the cloud top height and cloud top temperature with the intensity of the storm. Biondi et al (2012Biondi et al ( , 2013 showed a correlation between the cloud top altitude and the storm's thermal structure.…”
Section: Introductionmentioning
confidence: 99%
“…Second, given that the observed RO refractivity is higher than the weather model, the reliability of operational RO retrievals using the weather analyses temperatures is lower. Our ability to analyze the moist thermodynamics of precipitation from either weather model, as done in most of the available literature, or standard RO retrievals (e.g., Biondi et al, ; Biondi et al, ; Bonafoni & Biondi, ; Vergados et al, ) is lower and therefore one benefits from model‐independent validation. Those situations where weather models and RO differ are where RO soundings are most useful to identify and correct errors in the weather prediction models.…”
Section: Data and Approachmentioning
confidence: 99%